Assessing Distance Protection Systems’ Impact on the Dynamic Security of the Power System - رشيد سامر; تمام حيدر; سُميّا شروف (Latakia University Journal -Engineering Sciences Series, 2024)
Electrical power system security and reliability are considered to be the main tasks of transmission system operators (TSOs), but most research on power system security missed the assessment of the impacts of protection systems on system security. Therefore, in this paper, we present an assessment of the influences of the parameters and the functions of distance protection devices in transmission networks (especially the Direct Underreaching Transfer Trip function (DUTT)) upon the dynamic security of the power system. The effects of distance protection systems were analysed using a set of indices that are determined based on the number of pickups and unwanted operations with the corresponding time instants, as well as the amount of lost load and the time duration in which the impedance trajectory is inside the distance protection zones, throughout taking several contingencies into consideration. As a result of the assessment, we get a ranking of distance protection devices that is useful to highlight weak points of the protection system, we also get a ranking of contingencies that is useful to determine cascade tripping cases and critical system conditions after the fault. This enables the selection of the optimal algorithms for distance protection relays and thus ensures a more secure operation of the electrical power system.